Passive negative oxygen ion wall cloth and preparation method thereof

By optimizing the wall coating and cathode composite materials, and using nano tourmaline powder and other materials, a passive wall cloth that releases negative oxygen ions without electricity is achieved, solving the problem of insufficient energy consumption and coverage of active technology, and providing efficient and quiet Negative oxygen ion environment.

CN119261420APending Publication Date: 2025-01-07BEIJING TOPLI DECORATIVE MATERIALS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411370828.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing active negative oxygen ion technology has problems such as high energy consumption, limited negative ion coverage area, easy equipment damage and noise airflow disturbance, resulting in poor user experience.

Method used

Using the preparation method of passive negative oxygen ion wall cloth, nano tourmaline powder and N,N-dimethyl-β-hydroxyethyl octamide are used to optimize the composition of the wall coating composition and negative oxygen ion cathode composite material. Materials such as γ-propyl quaternary ammonium nitrate realize a permanent electrostatic field that releases negative oxygen ions without electricity, and improves the negative ion concentration and coverage area.

Benefits of technology

It realizes a high negative oxygen ion environment without noise and airflow disturbance, with excellent user experience, and avoids the consumption and quality impact of traditional cold glue composites, improving the film formation and quality of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005067531410000041
    Figure BDA0005067531410000041
Patent Text Reader

Abstract

The invention provides passive negative oxygen ion wall cloth and a preparation method thereof. The preparation method comprises the following steps: S1, stirring and mixing all the components of the wall cloth coating composition to prepare a mixture; s2, the mixture is subjected to internal mixing and then mixed, and a mixed material is prepared; s3, performing film pressing on the mixed material, thermally pasting a PVC film formed by film pressing on base cloth while the PVC film is hot, and performing cooling, printing and embossing to obtain a wall cloth printing and embossing semi-finished product; s4, mixing the components of the negative oxygen ion cathode composite material, and uniformly stirring under an ultrasonic condition to prepare the negative oxygen ion cathode composite material; s5, the negative oxygen ion cathode composite material and a printing medium are mixed and stirred uniformly, and slurry is prepared; and S6, uniformly coating the surface of the wall cloth printing and embossing semi-finished product with the slurry, and drying and cooling to obtain the passive negative oxygen ion wall cloth. The passive negative oxygen ion wall cloth can passively release a large number of negative oxygen ions, and the user experience feeling is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wall cloths, and in particular to a passive negative oxygen ion wall cloth and a preparation method thereof. Background Art

[0002] Negative oxygen ion wall covering is a new type of wall covering that can release a large amount of negative oxygen ions that are beneficial to human physical and mental health. It is mainly composed of inorganic minerals and pure natural ingredients, has no toxic side effects, and has the function of permanently releasing hydroxyl negative ions. Existing negative oxygen ion wall coverings mainly add natural minerals such as nano seagull stone and ancient sea rock as negative oxygen ion materials. The concentration of negative oxygen ions that can be released is low, and the coverage area of ​​negative oxygen ions is limited, so the actual application effect is not good.

[0003] The existing active negative oxygen ion generation technology mainly processes the input DC or AC power through special treatment, and then upgrades it to AC high voltage through pulse circuits and high-voltage isolation lines, and then obtains pure DC negative high voltage after rectification and filtering through special grade electronic materials. The DC negative high voltage is connected to the release tip made of metal or carbon elements, and the DC high voltage at the tip is used to generate high corona, releasing a large number of electrons at high speed. These electrons cannot exist in the air for a long time and will be immediately captured by oxygen molecules in the air, thereby generating negative air ions.

[0004] However, active negative oxygen ion technology has the following problems when applied to indoor spaces: 1) Negative ion generators consume a lot of electricity, resulting in energy consumption; 2) Negative ions exist in space for a very short time, and it is impossible to rely on machines to achieve full coverage of negative oxygen ions in the space; 3) Negative ion generators are in a high-voltage discharge state for a long time, the equipment is extremely easy to be damaged, and the subsequent maintenance cost is high; 4) Negative ion generators will cause noise and airflow disturbances, resulting in a poor experience.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a passive negative oxygen ion wall cloth and a preparation method thereof. The passive negative oxygen ion wall cloth can passively release a large amount of negative oxygen ions, and the user experience is excellent.

[0007] The present invention provides a method for preparing a passive negative oxygen ion wall covering, comprising the following steps:

[0008] S1: adding the components according to the composition of the wall cloth coating composition into a high-stirring mixing device and stirring and mixing to obtain a mixture;

[0009] S2: conveying the mixed material to a mixing chamber for mixing, and conveying the mixed material to a twin-roll extruder for mixing to obtain a mixed material;

[0010] S3: conveying the mixed material to a laminator for lamination, laminating the PVC film formed by lamination onto the base fabric while hot, cooling it through a cooling roller, and then printing and embossing it through a gravure printing machine to obtain a semi-finished wall cloth with printed and embossed patterns;

[0011] S4: mixing the components according to the composition of the negative oxygen ion cathode composite material and stirring them evenly under ultrasonic conditions to obtain the negative oxygen ion cathode composite material;

[0012] S5: mixing the negative oxygen ion cathode composite material and the printing medium and stirring them evenly to prepare a negative oxygen ion cathode composite slurry;

[0013] S6: The negative oxygen ion cathode composite slurry is evenly coated on the surface of the printed embossed semi-finished wall cloth, and after drying and cooling, a passive negative oxygen ion wall cloth is obtained.

[0014] In step S1, the wall cloth coating composition includes the following components in parts by weight: 100 parts of PVC resin, 30-35 parts of DOTP, 4-6 parts of epoxy soybean oil, 2-3 parts of composite calcium zinc stabilizer, 18-22 parts of stone powder, 28-32 parts of aluminum hydroxide, 4-6 parts of environmentally friendly flame retardant, 13-15 parts of titanium dioxide and 0.2-0.4 parts of stearic acid; the composite calcium zinc stabilizer includes calcium zinc stabilizer and barium zinc stabilizer, and the mass ratio of calcium zinc stabilizer to barium zinc stabilizer in the composite calcium zinc stabilizer is 1: (1-2); the mixture is stirred and mixed at 40-50°C for 4-6 minutes. By optimizing the composition of the wall cloth coating composition, the film-forming quality of the PVC film is improved.

[0015] In step S2, the mixture is kneaded at 130-140° C. for 5-10 min; the mixing time is 3-5 min.

[0016] In step S3, the hot lamination temperature is 165-185°C, for example, 170-180°C; the printing temperature is 90-120°C, and the embossing temperature is 185-205°C, for example, 200-205°C. The PVC film formed by lamination is hot-laminated onto the base fabric while hot, which can form a better lamination effect, good firmness and durability of lamination, and can effectively avoid the generation of VOC and static electricity during traditional cold glue lamination, avoid the adverse effects of VOC and static electricity such as consumption of negative oxygen ions and affecting product quality, and improve the product quality of the wall cloth.

[0017] In step S4, the negative oxygen ion cathode composite material includes the following components in parts by weight: 45-55 parts of modified acrylic emulsion, 0.5-1.5 parts of defoamer, 1.5-2.5 parts of N,N-dimethyl-β-hydroxyethyl octadecanoyl γ-propyl quaternary ammonium nitrate, 25-35 parts of modified nano-tourmaline powder and 15-25 parts of tert-butyl vinyl carbonate; the modified nano-tourmaline powder is composed of nano-tourmaline powder and borate, and the weight ratio of nano-tourmaline powder to borate is (3-5): (5-7); the mass ratio of the negative oxygen ion cathode composite material to the printing medium is (10-20): (80-90); the printing medium is a water-based acrylic printing medium; the stirring temperature is 30-40°C, and the stirring time is 20-40min.

[0018] Nano-tourmaline is a borosilicate mineral with complex structure and composition, belonging to the trigonal crystal system. Since there are 5 polyhedrons in tourmaline, when the pressure or temperature acting on the crystal surface changes, the polyhedrons inside it will be distorted, among which the T polyhedron is the most distorted, so polarized charges appear on the two crystal end faces perpendicular to the c-axis, which is manifested macroscopically as a permanent electrostatic field around the tourmaline that is not affected by the external electric field.

[0019] When the pressure or temperature acting on the crystal surface changes, the external stress or thermal expansion of the crystal can polarize the unidirectional polar axis c-axis in the tourmaline crystal, and the charged particles in the crystal will be relatively displaced, and the positive and negative charge centers will shift along the c-axis, causing the total electrode moment of the crystal to change. The generated polarization charge is much larger than the spontaneous polarization effect, which makes the tourmaline have piezoelectric effect and pyroelectric effect, and has a strong far-infrared radiation function. At the same time, temperature and pressure changes will also cause the potential difference of the tourmaline crystal, ionizing the surrounding air, and the struck electrons will act on the nearby water and oxygen molecules and convert them into negative oxygen ions.

[0020] In addition, studies have shown that the ability of nano-tourmaline powder to release negative oxygen ions is closely related to its particle size and distribution; the present invention uses tert-butyl vinyl carbonate and modified acrylic emulsion as low-temperature dispersion and attachment carriers and compound defoaming agents, and stirring under constant temperature ultrasonic waves can activate and disperse the nano-tourmaline powder to the greatest extent, thereby improving the ability of nano-tourmaline to release negative oxygen ions and greatly improving the negative ion concentration in the space.

[0021] The molecular formula of N,N-dimethyl-β-hydroxyethyl octadecanoylamide γ-propyl quaternary ammonium nitrate is as follows:

[0022]

[0023] N,N-dimethyl-β-hydroxyethyl octadecanoylamide γ-propyl quaternary ammonium nitrate can be evenly distributed in PVC and nano-tourmaline coatings. Its molecular structure and anionic properties enable it to eject negative oxygen ions into the air like a spring, making the dispersion of negative oxygen ions more uniform and extensive, significantly increasing the negative ion coverage area in the space. In addition, N,N-dimethyl-β-hydroxyethyl octadecanoylamide γ-propyl quaternary ammonium nitrate and tert-butyl ester can improve the film-forming properties of passive negative oxygen ion wall cloth, making the appearance and quality of passive negative oxygen ion wall cloth better.

[0024] The preparation method of the present invention adopts a method of first performing normal printing and embossing and then processing the negative oxygen ion material, which can maximize the use of the characteristics of the negative oxygen ion material to stimulate negative oxygen ions; in addition, by optimizing the composition of the negative oxygen ion cathode material, the ability of nano-tourmaline to release negative oxygen ions can be maximized, thereby significantly improving the negative ion concentration and coverage area in the space.

[0025] In step S5, the stirring speed is 1100-1300 r / min, and the stirring time is 5-15 min.

[0026] In step S6, the coating amount is 20-25 g / m 2 ; The vehicle speed is 15-25 m / min and the temperature is 90-150℃.

[0027] The present invention also provides a passive negative oxygen ion wall cloth, which is prepared according to the above preparation method.

[0028] The preparation method of the present invention prepares the wall cloth coating composition into a PVC film, and hot-bonds the PVC film to the base cloth while it is hot, which not only improves the bonding effect, but also avoids the adverse effects of the traditional cold glue composite process caused by the generation of VOC and static electricity, such as consumption of negative oxygen ions and affecting product quality; in particular, by optimizing the composition of the negative oxygen ion cathode composite material, using different molecular materials, and utilizing the temperature difference and pressure difference in the air, negative oxygen ions are formed on the surface of the material, and electron ejection is achieved through the cathode electrostatic molecular functional group, so that the negative oxygen ions can be distributed more widely in the space; in addition, the practical characteristics of the wall cloth that requires the whole house to be decorated are utilized, so as to realize the passive release of a large amount of negative oxygen ions in the whole space without using electrical energy or other chemical energy, so that the whole space realizes a high negative oxygen ion environment, which has both the harmony and beauty of the overall space and the healthy environment of high negative oxygen ions, and is quiet, noiseless, and free of airflow disturbance, with an excellent experience. DETAILED DESCRIPTION

[0029] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0030] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The raw materials used in each embodiment are as follows:

[0033] PVC resin: Type V suspension PVC resin, model S-1000, viscosity 1.87-1.89, water content 0.05-0.08%, purchased from Beijing Zhonghe Yongchang Economic and Trade Co., Ltd.;

[0034] Epoxidized soybean oil: model HM-01AD, purchased from Suzhou Easeo New Material Technology Co., Ltd.;

[0035] Stone powder: model CC-902, oil absorption value 35-38%, moisture 0.04-0.08%, purchased from Guangxi Hezhou Kelong Powder Co., Ltd.;

[0036] Environmentally friendly flame retardant: purchased from Liuyang Baolin Electrical New Materials Co., Ltd.;

[0037] Modified acrylic emulsion: model EMX-6A, solid content 21-24%, pH value 7.5, purchased from Shanghai Dongxing Environmental Protection Ink Co., Ltd.;

[0038] Nano tourmaline powder: particle size 2000 mesh, purchased from Beijing Senhai Oxygen Source Technology Co., Ltd.;

[0039] Defoaming agent: stearyl alcohol purchased from Shanghai Dongxing Environmental Protection Ink Co., Ltd.

[0040] N,N-dimethyl-β-hydroxyethyl octadecanoamide γ-propyl quaternary ammonium nitrate: purchased from Polyli Chemical;

[0041] Water-based acrylic printing medium: model EMW, pH value 7.5-9.5, viscosity (No. 3 Zahn cup, 25° C.) 15-50 seconds, fineness better than 25 μm, purchased from Shanghai Dongxing Environmental Protection Ink Co., Ltd.

[0042] Example 1

[0043] The preparation method of the passive negative oxygen ion wall cloth of this embodiment comprises the following steps:

[0044] 1. Prepare the ingredients

[0045] The wall cloth coating composition is prepared according to the following components in parts by weight: 100 parts of PVC resin, 32 parts of DOTP, 5 parts of epoxidized soybean oil, 2.5 parts of composite calcium-zinc stabilizer, 20 parts of stone powder, 30 parts of aluminum hydroxide, 5 parts of environmentally friendly flame retardant, 14 parts of titanium dioxide and 0.3 parts of stearic acid; wherein the composite calcium-zinc stabilizer is composed of a calcium-zinc stabilizer and a barium-zinc stabilizer, and the mass ratio of the calcium-zinc stabilizer to the barium-zinc stabilizer is 1:1.

[0046] 2. Preparation of wall cloth printing and embossing semi-finished products

[0047] Add the components of the wall cloth coating composition to a high-stirring mixing equipment according to their weight portions, and stir and mix at 45°C for 5 minutes; when adding the materials, add the PVC resin first, then add the liquid components, premix for 2 minutes, then add the other powder components, and mix at room temperature for 3 minutes to obtain a mixture.

[0048] The above mixture is conveyed to the mixing chamber, the temperature is set to 135℃, and the mixing is carried out for 8 minutes; after the mixing is completed, the mixture is further conveyed to the double-roll extruder for mixing for 4 minutes. After mixing, the material is quantitatively conveyed to the 4-roll film pressing machine for film pressing, and the film (i.e. PVC film) is hot-laminated on the cross cloth while hot, and the hot lamination temperature is 170℃, and then cooled by the cooling roller, and then the above semi-finished wall cloth is printed and embossed by the gravure printing machine with different patterns and colors. The printing temperature of each plate is controlled at 90℃, and the embossing temperature is controlled at 200℃ to obtain the printed and embossed semi-finished wall cloth.

[0049] 3. Preparation of negative oxygen ion cathode composite slurry

[0050] The negative oxygen ion cathode material is prepared according to the following components in parts by weight: 50 parts of modified acrylic emulsion, 1 part of defoamer, 2 parts of N,N-dimethyl-β-hydroxyethyl octadecanoyl γ-propyl quaternary ammonium nitrate, 30 parts of modified nano-tourmaline powder and 17 parts of versatate; wherein the modified nano-tourmaline powder consists of nano-tourmaline powder (2000 mesh) and sodium borate, and the weight ratio of nano-tourmaline powder to sodium borate is 1:1.

[0051] The above components were mixed according to weight ratio and in the order of adding the liquid component first and then the powder component, and stirred in an ultrasonic constant temperature bath at 35° C. for 30 minutes to obtain a negative oxygen ion cathode material.

[0052] 20 parts of the above negative oxygen ion cathode material were mixed with 80 parts of aqueous acrylic printing medium, and stirred at 1200 r / min for 10 minutes to prepare a negative oxygen ion cathode composite slurry.

[0053] 4. Preparation of passive negative oxygen ion wall covering

[0054] The negative oxygen ion cathode composite slurry is evenly coated on the surface of the wall cloth printed embossed semi-finished product by squeezing using an upper silicone roller and a lower silicone roller with a hardness of 72 on a printing machine, and the coating amount is 20g / m 2 ; Then, according to the depth of the wall cloth texture, set the vehicle speed to 15 m / min and the temperature to 120°C, dry at 100°C for 30s, cool and trim, and separate into 30 m / rolls according to standards to obtain passive negative oxygen ion wall cloth.

[0055] Example 2

[0056] The preparation method of the passive negative oxygen ion wall cloth of this embodiment comprises the following steps:

[0057] 1. Prepare the ingredients

[0058] The wall cloth coating composition is prepared according to the following components in parts by weight: 100 parts of PVC resin, 30 parts of DOTP, 5 parts of epoxidized soybean oil, 2 parts of composite calcium-zinc stabilizer, 20 parts of stone powder, 28 parts of aluminum hydroxide, 4 parts of environmentally friendly flame retardant, 14 parts of titanium dioxide and 0.2 parts of stearic acid; wherein the composite calcium-zinc stabilizer is composed of a calcium-zinc stabilizer and a barium-zinc stabilizer, and the mass ratio of the calcium-zinc stabilizer to the barium-zinc stabilizer is 1:2.

[0059] 2. Preparation of wall cloth printing and embossing semi-finished products

[0060] Add the components of the wall cloth coating composition to a high-stirring mixing equipment according to their weight portions, and stir and mix at 45°C for 5 minutes; when adding the materials, add the PVC resin first, then add the liquid components, premix for 2 minutes, then add the other powder components, and mix at room temperature for 3 minutes to obtain a mixture.

[0061] The above mixture was transported to a mixing chamber, the temperature was set to 135°C, and the mixing was performed for 8 minutes; after the mixing was completed, the mixture was further transported to a twin-roll extruder for mixing for 4 minutes. After mixing, the material was quantitatively transported to a 4-roll laminating machine for laminating, and the film was hot-laminated onto the cross cloth while hot, the hot laminating temperature was 175°C, and then cooled by a cooling roller, and then the above semi-finished wall cloth was printed and embossed by a gravure printing machine with different patterns and colors, the printing temperature of each plate was controlled at 100°C, and the embossing temperature was controlled at 205°C, to obtain a printed and embossed semi-finished wall cloth.

[0062] 3. Preparation of negative oxygen ion cathode composite slurry

[0063] The negative oxygen ion cathode material is prepared according to the following components in parts by weight: 50 parts of modified acrylic emulsion, 1 part of defoamer, 2 parts of N,N-dimethyl-β-hydroxyethyl octadecanoyl γ-propyl quaternary ammonium nitrate, 32 parts of modified nano-tourmaline powder and 18 parts of versatate; wherein the modified nano-tourmaline powder consists of nano-tourmaline powder (2000 mesh) and sodium borate, and the weight ratio of nano-tourmaline powder to sodium borate is 3:7.

[0064] The above components were mixed according to weight ratio and in the order of adding the liquid component first and then the powder component, and stirred in an ultrasonic constant temperature bath at 30° C. for 40 minutes to obtain a negative oxygen ion cathode material.

[0065] 15 parts of the above negative oxygen ion cathode material were mixed with 85 parts of aqueous acrylic printing medium, and stirred at 1200 r / min for 10 minutes to prepare a negative oxygen ion cathode composite slurry.

[0066] 4. Preparation of passive negative oxygen ion wall covering

[0067] The negative oxygen ion cathode composite slurry is evenly coated on the surface of the wall cloth printed embossed semi-finished product by squeezing using an upper silicone roller and a lower silicone roller with a hardness of 72 on a printing machine, and the coating amount is 20g / m 2 ; Then, according to the depth of the wall cloth texture, set the vehicle speed to 20 m / min and the temperature to 130°C, dry at 120°C for 20s, cool and trim, and separate into 30 m / rolls according to standards to produce passive negative oxygen ion wall cloth.

[0068] Example 3

[0069] The preparation method of the passive negative oxygen ion wall cloth of this embodiment comprises the following steps:

[0070] 1. Prepare the ingredients

[0071] The wall cloth coating composition is prepared according to the following components in parts by weight: 100 parts of PVC resin, 34 parts of DOTP, 5 parts of epoxidized soybean oil, 3 parts of composite calcium-zinc stabilizer, 20 parts of stone powder, 28 parts of aluminum hydroxide, 6 parts of environmentally friendly flame retardant, 13 parts of titanium dioxide and 0.3 parts of stearic acid; wherein the composite calcium-zinc stabilizer is composed of a calcium-zinc stabilizer and a barium-zinc stabilizer, and the mass ratio of the calcium-zinc stabilizer to the barium-zinc stabilizer is 1:1.5.

[0072] 2. Preparation of wall cloth printing and embossing semi-finished products

[0073] Add the components of the wall cloth coating composition to a high-stirring mixing equipment according to their weight portions, and stir and mix at 45°C for 5 minutes; when adding the materials, add the PVC resin first, then add the liquid components, premix for 3 minutes, then add the other powder components, and mix at 45°C for 3 minutes to obtain a mixture.

[0074] The above mixture was transported to a mixing chamber, the temperature was set to 135°C, and the mixing was performed for 8 minutes; after the mixing was completed, the mixture was further transported to a twin-roll extruder for mixing for 5 minutes. After mixing, the material was quantitatively transported to a 4-roll laminating machine for laminating, and the film was hot-laminated onto the cross cloth while hot, the hot laminating temperature was 180°C, and then cooled by a cooling roller, and then the above semi-finished wall cloth was printed and embossed by a gravure printing machine with different patterns and colors, the printing temperature of each plate was controlled at 120°C, and the embossing temperature was controlled at 205°C, to obtain a printed and embossed semi-finished wall cloth.

[0075] 3. Preparation of negative oxygen ion cathode composite slurry

[0076] The negative oxygen ion cathode material is prepared according to the following components in parts by weight: 50 parts of modified acrylic emulsion, 1.5 parts of defoaming agent, 2 parts of N,N-dimethyl-β-hydroxyethyl octadecanoyl γ-propyl quaternary ammonium nitrate, 32 parts of modified nano-tourmaline powder and 18 parts of tert-butyl vinyl carbonate; wherein the modified nano-tourmaline powder is composed of nano-tourmaline powder (2000 mesh) and sodium borate, and the weight ratio of nano-tourmaline powder to sodium borate is 4:6.

[0077] The above components were mixed according to weight ratio and in the order of adding the liquid component first and then the powder component, and stirred in an ultrasonic constant temperature bath at 40° C. for 20 minutes to obtain a negative oxygen ion cathode material.

[0078] 10 parts of the above negative oxygen ion cathode material were mixed with 90 parts of aqueous acrylic printing medium, and stirred at 1200 r / min for 10 minutes to prepare a negative oxygen ion cathode composite slurry.

[0079] 4. Preparation of passive negative oxygen ion wall covering

[0080] The negative oxygen ion cathode composite slurry is evenly coated on the surface of the wall cloth printed embossed semi-finished product by squeezing using an upper silicone roller and a lower silicone roller with a hardness of 72 on a printing machine, and the coating amount is 20g / m 2 ; Then, according to the depth of the wall cloth texture, set the vehicle speed to 25 m / min, the temperature to 150°C, dry at 110°C for 30s, cool and trim, and separate into 30 m / roll according to the standard to obtain passive negative oxygen ion wall cloth.

[0081] Comparative Example 1

[0082] Except for the different composition of the negative oxygen ion cathode material, the rest is the same as Example 1.

[0083] The negative oxygen ion cathode material of this control example includes the following components in parts by weight: 50 parts of modified acrylic emulsion, 1 part of defoamer, 2 parts of N,N-dimethyl-β-hydroxyethyl octadecanoamide γ-propyl quaternary ammonium nitrate, 15 parts of nano-tourmaline powder (2000 mesh) and 17 parts of versatate.

[0084] Comparative Example 2

[0085] Except for the different composition of the negative oxygen ion cathode material, the rest is the same as Example 1.

[0086] The negative oxygen ion cathode material of this control example includes the following components in parts by weight: 50 parts of modified acrylic emulsion, 1 part of defoaming agent, 30 parts of modified nano-tourmaline powder and 19 parts of tert-butyl vinyl carbonate; wherein the modified nano-tourmaline powder is composed of nano-tourmaline powder (2000 mesh) and sodium borate, and the weight ratio of nano-tourmaline powder to sodium borate is 1:1.

[0087] Comparative Example 3

[0088] Except for the different composition of the negative oxygen ion cathode material, the rest is the same as Example 1.

[0089] The negative oxygen ion cathode material of this control example includes the following components in parts by weight: 67 parts of modified acrylic emulsion, 1 part of defoamer, 2 parts of N,N-dimethyl-β-hydroxyethyl octadecanoamide γ-propyl quaternary ammonium nitrate and 30 parts of modified nano-tourmaline powder; wherein the modified nano-tourmaline powder is composed of nano-tourmaline powder (2000 mesh) and sodium borate, and the weight ratio of nano-tourmaline powder to sodium borate is 1:1.

[0090] Comparative Example 4

[0091] The process is the same as that of Example 1 except that anionic polyacrylamide (APAM) replaces the N,N-dimethyl-β-hydroxyethyl octadecanoylamide γ-propyl quaternary ammonium nitrate of Example 1.

[0092] Comparative Example 5

[0093] Except that the negative oxygen ion cathode material of Example 1 is replaced by a negative oxygen ion material, the rest is basically the same as Example 1.

[0094] The negative oxygen ion material composition of this control example is as follows: 20 parts of negative oxygen ion material (mineral powder produced in Lingshou County, purchased from the normal market) are mixed with 80 parts of water-based acrylic printing medium, stirred at 1200r / min for 10 minutes to obtain negative oxygen ion slurry; negative oxygen ion wall cloth is obtained.

[0095] Comparative Example 6

[0096] The process is the same as that of Example 1 except that the PVC film prepared in Example 1 is laminated to the cross cloth by cold glue lamination.

[0097] Test Example 1

[0098] The negative ion performance of the negative oxygen ion wall coverings of each embodiment and reference example was tested using the following method:

[0099] Negative ion concentration: using the material-induced air ion test method;

[0100] Negative ion free distance: Post 1 square meter of negative oxygen ion wall cloth, test the concentration of negative oxygen ions at different distances in a closed room, and the average value reaches 500ions / cm 3 The above position is the free distance of negative oxygen ions.

[0101] The results are shown in Table 1.

[0102] Table 1 Quality test results of each negative oxygen ion wall cloth

[0103] Negative oxygen ion wall covering <![CDATA[Negative ion concentration (ions / cm 3 )]]> Negative ion free distance (m) Example 1 11500 2.52 Example 2 6580 1.90 Example 3 5260 1.50 Comparative Example 1 5900 1.78 Comparative Example 2 7450 1.60 Comparative Example 3 8100 1.72 Comparative Example 4 7900 1.68 Comparative Example 5 2910 1.00 Comparative Example 6 5680 1.65

[0104] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a passive negative oxygen ion wall cloth, characterized in that: The steps include: S1: adding the components according to the composition of the wall cloth coating composition into a high-stirring mixing device and stirring and mixing to obtain a mixture; S2: conveying the mixed material to a mixing chamber for mixing, and conveying the mixed material to a twin-roll extruder for mixing to obtain a mixed material; S3: conveying the mixed material to a laminator for lamination, laminating the PVC film formed by lamination onto the base fabric while hot, cooling it through a cooling roller, and then printing and embossing it through a gravure printing machine to obtain a semi-finished wall cloth with printed and embossed patterns; S4: mixing the components according to the composition of the negative oxygen ion cathode composite material and stirring them evenly under ultrasonic conditions to obtain the negative oxygen ion cathode composite material; S5: mixing the negative oxygen ion cathode composite material and the printing medium and stirring them evenly to prepare a negative oxygen ion cathode composite slurry; S6: The negative oxygen ion cathode composite slurry is evenly coated on the surface of the printed embossed semi-finished wall cloth, and after drying and cooling, a passive negative oxygen ion wall cloth is obtained.

2. The preparation method according to claim 1, characterized in that: In step S1, the wall cloth coating composition includes the following components in parts by weight: 100 parts of PVC resin, 30-35 parts of DOTP, 4-6 parts of epoxidized soybean oil, 2-3 parts of composite calcium zinc stabilizer, 18-22 parts of stone powder, 28-32 parts of aluminum hydroxide, 4-6 parts of environmentally friendly flame retardant, 13-15 parts of titanium dioxide and 0.2-0.4 parts of stearic acid.

3. The preparation method according to claim 2, characterized in that: The composite calcium zinc stabilizer comprises a calcium zinc stabilizer and a barium zinc stabilizer, and the mass ratio of the calcium zinc stabilizer to the barium zinc stabilizer in the composite calcium zinc stabilizer is 1:(1-2).

4. The preparation method according to claim 1, characterized in that: In step S1, the mixture is stirred and mixed at 40-50°C for 4-6 minutes; in step S2, the mixture is kneaded at 130-140°C for 5-10 minutes; the kneading time is 3-5 minutes; in step S3, the thermal bonding temperature is 165-185°C, the printing temperature is 90-120°C, and the embossing temperature is 185-205°C.

5. The preparation method according to claim 1, characterized in that: In step S4, the negative oxygen ion cathode composite material includes the following components in parts by weight: 45-55 parts of modified acrylic emulsion, 0.5-1.5 parts of defoamer, 1.5-2.5 parts of N,N-dimethyl-β-hydroxyethyl octadecanoylamide γ-propyl quaternary ammonium nitrate, 25-35 parts of modified nano-tourmaline powder and 15-25 parts of versatate.

6. The preparation method according to claim 5, characterized in that: The modified nano tourmaline powder is composed of nano tourmaline powder and borate, and the weight ratio of the nano tourmaline powder to the borate is (3-5): (5-7).

7. The preparation method according to claim 1, characterized in that: In step S4, the mass ratio of the negative oxygen ion cathode composite material to the printing medium is (10-20): (80-90); preferably, the printing medium is a water-based acrylic printing medium.

8. The preparation method according to claim 1, characterized in that: In step S4, the stirring temperature is 30-40°C and the stirring time is 20-40 min; in step S5, the stirring speed is 1100-1300 r / min and the stirring time is 5-15 min.

9. The preparation method according to claim 1, characterized in that: In step S6, the coating amount is 20-25 g / m 2 ; The vehicle speed is 15-25 m / min and the temperature is 90-150℃.

10. A passive negative oxygen ion wall covering, characterized in that: Prepared according to any one of the preparation methods of claims 1-9.

Citation Information

Patent Citations

  • Production method of wall covering fabric or wall cloth

    CN103434246A

  • High-strength flame-retardant mould-proof embossed wall cloth and production technology thereof

    CN105058936A

  • Odor-free formaldehyde-free interior wall environmentally friendly coating and preparation method thereof

    CN106752555A

  • Environmentally-friendly fireproof wallpaper and production method thereof

    CN107489073A

  • Anion wall cloth

    CN207812888U